Technology Matters: SPARX – computerised cognitive behavioural therapy for adolescent depression in a game format. Issue 1 (4th January 2021) - Fleming, Theresa; Lucassen, Mathijs; Stasiak, Karolina; Sutcliffe, Kylie; Merry, Sally
Abstract : Adolescent depression is common, and its prevalence is thought to be increasing in many high income nations. Addressing adolescent depression has proven challenging using traditional face‐to‐face psychotherapies, with major barriers including workforce shortages internationally and reluctance to seek help among some adolescents. There is substantial evidence to support the use of digital tools to treat mental health problems, with the National Institute for Health and Care Excellence (NICE) now recommending such tools as a first‐line treatment. In this article, we outline the evidence base for SPARX, a digital tool named specifically in NICE guideline NG134, and discuss its use in clinical settings. We also consider implementation issues and future research directions.